Employee Performance Apparaisal Using Decision Support System by AHP and TOPSIS Methods - Achmad Baroqah Pohan; Sofian Wira Hadi; Syaifur Rahmatullah; Robi Aziz Zuama; Achmad Rifai; Deni Gunawan (Universitas Bina Sarana Informatika, 2021)
During this time the performance appraisal of PT. Injep Inti Cemerlang has not been implemented optimally, especially in employee performance appraisal. Performance appraisal so far is only determined from the results, there are no clear appraisal criteria. Based on this reason, a decision support system is needed to help find the best alternative for the employees selection. In this research a decision support system for employee performance appraisal will be developed based on Attitude, Responsibility, Attendance, Discipline and Collaboration. This research aims to design a decision support system for employee performance appraisal using data collection methods by observation, interviews and giving questionnaires to employees of PT. Injep Inti Cemerlang. The data collected is carried out the process of analyzing data and looking for weighting values using the AHP method and for ranking using the TOPSIS method, where each criterion is appraisal factors and alternatives in this case employees are compared the criteria that have been weighted through the process of calculating the AHP and TOPSIS method starting from giving the weighting of criteria by calculating with Ms. Excel and calculating with Expert Choice software. The results have been obtained from weighting the next ranking by the TOPSIS method. thus providing a value output that results in a system that employees appraisal. This decision support system helps the employee performance apprasial at PT. Injep Inti Cemerlang in determining the employee who has the best performance